Evaluation with micro‐CT of different anticoagulation strategies during hemodialysis in patients with thrombocytopenia: A randomized crossover study. Issue 8 (7th April 2019) - Vanommeslaeghe, Floris; De Somer, Filip; Josipovic, Iván; Boone, Matthieu; Dhondt, Annemieke; Van Biesen, Wim; Eloot, Sunny
Abstract: In patients with enhanced risk for bleeding, heparin‐free hemodialysis (HD) with conventional dialyzers is routinely used. To explore the potential benefit of using heparin‐coated dialyzers, we used a reference CT‐scanning technique and registered different clotting parameters to quantify coagulation with heparin‐coated versus non‐coated dialyzers. Six HD patients with thrombocytopenia were dialyzed 240 min in a randomized crossover study with Evodial 1.3 or FX600 Cordiax, each without anticoagulation. Blood samples were taken from the vascular access predialysis, and from the dialyzer inlet and outlet at 5 and 240 min after dialysis start. Predialysis blood samples were analyzed for hemoglobin, hematocrit, thrombocytes, fibrinogen, and activated partial thromboplastin time. On dialyzer inlet and outlet blood samples, a viscoelastic measurement of blood coagulation was performed using a Sonoclot analyzer. After dialysis, dialyzers were visually scored, subsequently dried for 24 h, weighed, and scanned with micro‐CT at a resolution of 25 µm. After image reconstruction, the open, non‐coagulated fibers were counted in a representative cross‐section at the dialyzer outlet. No sessions were terminated prematurely for circuit clotting. Heparin‐coated dialyzers had more patent fibers on micro‐CT versus non‐coated dialyzers and also had a better score of subjective visual assessment of fiber clotting. There was no difference in subjective assessment of clotting at the venous drip chamber. With both dialyzers, all ACT values remained in the normal range, and were lower at the dialyzer outlet versus inlet. In conclusion, dialysis with a heparin‐coated versus non heparin‐coated membrane results in substantially less coagulated fibers during 4 h hemodialysis without systemic anticoagulation. Eventual leaching of heparin, immobilized on the fiber membrane, does not result in measurable systemic anticoagulation.